2020
DOI: 10.1080/02813432.2020.1717087
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial issues need more attention in COPD self-management education

Abstract: Objective: To find out how regularly the contents of patient education regarded as essential for COPD patients' self-management are provided by healthcare professionals in specialised healthcare (SHC) and primary healthcare (PHC) in Finland. Design: A cross-sectional study based on an e-questionnaire with 42 items on the content of self-management education of COPD patients. Setting: The study sample included all public SHC units with pulmonary outpatient clinics (n ¼ 29) and nine out of 160 health centres in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The items were developed for this study using previous systematic reviews (Stoilkova et al., 2013 ; Tan et al., 2012 ), a questionnaire (Bristol COPD knowledge questionnaire (BCKQ); White et al., 2006 ), clinical pathways (NICE, 2016 ) and the Finnish guidelines for COPD management (Kankaanranta et al., 2015 ). Moreover, a previous study of healthcare professionals’ perceptions of counselling was used due to the holistic approach of the questionnaire employed in that study (Siltanen et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The items were developed for this study using previous systematic reviews (Stoilkova et al., 2013 ; Tan et al., 2012 ), a questionnaire (Bristol COPD knowledge questionnaire (BCKQ); White et al., 2006 ), clinical pathways (NICE, 2016 ) and the Finnish guidelines for COPD management (Kankaanranta et al., 2015 ). Moreover, a previous study of healthcare professionals’ perceptions of counselling was used due to the holistic approach of the questionnaire employed in that study (Siltanen et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the SIGN checklist, 18 of the studies [ 7 , 20 , 28 , 30 , 31 , 33 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 49 , 55 ] were rated “high quality” and 17 studies were “acceptable quality” [ 5 , 6 , 15 , 19 , 29 , 34 , 36 , 46 , 47 , 48 , 50 , 51 , 52 , 53 , 54 , 56 ]. Although the studies were rated as being high and acceptable quality, for sample selection random assignment was used and no detailed description of the procedure was provided.…”
Section: Resultsmentioning
confidence: 99%
“…Other health education initiatives have reflected on the role of health education professionals to ensure that there are no gaps in access to educational programs [ 18 ]. Furthermore, it is considered that the training processes of health professionals should be continuous and cover not only the clinical or physical aspects, but also the psychosocial aspects of a population [ 19 ]. In this regard, health education should be provided holistically by various professionals who have both updated knowledge and adequate skills.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients in our study reported symptoms of depression and anxiety under the level that could indicate a diagnosis of depression or anxiety disorder, but it seems that even symptoms at this low level are negatively associated with the patient’s self-efficacy. A recent study showed that issues like psychological well-being, stress and fatigue often are underemphasized in self-management education [ 34 ]. Discussing these issues and supporting the patients in finding strategies will possibly facilitate rehabilitation efforts.…”
Section: Discussionmentioning
confidence: 99%